2014
DOI: 10.1371/journal.pone.0084401
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Comparison of the Behavior of Human Ventricular Cardiac Electrophysiology Models in Tissue

Abstract: Numerical integration of mathematical models of heart cell electrophysiology provides an important computational tool for studying cardiac arrhythmias, but the abundance of available models complicates selecting an appropriate model. We study the behavior of two recently published models of human ventricular action potentials, the Grandi-Pasqualini-Bers (GPB) and the O'Hara-Virág-Varró-Rudy (OVVR) models, and compare the results with four previously published models and with available experimental and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…(1) is specified by a particular cellular model. To our knowledge, reliable information about the structure of electrical turbulence during ventricular fibrillation is lacking, as cellular models are built to reproduce the activity in single cells and even recent models of human ventricular cells exhibit a very diverse spatiotemporal behavior 31 . Thus, we tested several cellular models which exhibit qualitatively different spatiotemporal chaos: The Luo-Rudy (LR) model with standard parameter values 32 , the Ten Tusscher (TT) model with parameter values to match human epicardial tissue 33 , and the Fenton-Karma (FK) model 34 .…”
Section: A Mono-domain Equation and Cellular Modelsmentioning
confidence: 99%
“…(1) is specified by a particular cellular model. To our knowledge, reliable information about the structure of electrical turbulence during ventricular fibrillation is lacking, as cellular models are built to reproduce the activity in single cells and even recent models of human ventricular cells exhibit a very diverse spatiotemporal behavior 31 . Thus, we tested several cellular models which exhibit qualitatively different spatiotemporal chaos: The Luo-Rudy (LR) model with standard parameter values 32 , the Ten Tusscher (TT) model with parameter values to match human epicardial tissue 33 , and the Fenton-Karma (FK) model 34 .…”
Section: A Mono-domain Equation and Cellular Modelsmentioning
confidence: 99%
“…This maneuver was previously tested and validated by ElShrif et al [39]. In this study, using the TNNP formulation of I Na in ORd model, conduction velocity (CV) yielded values that closely matched experimental data [40] and could also replicate the main characteristics of I Na, restitution properties and spiral wave behavior [39].…”
Section: Methodsmentioning
confidence: 74%
“…This maneuver was previously tested and validated by ElShrif et al [39]. In this study, using the TNNP formulation of I Na in ORd model, conduction velocity (CV) yielded values that closely matched experimental data [40] and could also replicate the main characteristics of I Na, restitution properties and spiral wave behavior [39]. To illustrate the behavior of this modified model, Fig 1 shows the comparison of the main ion currents, AP and ion concentrations of the original ORd model and the modified model used in the present study and in [39].…”
Section: Methodsmentioning
confidence: 99%
“…Previous authors have made quantitative comparisons in the behavior of models for cardiac EP and found that they differ [5]. Other works have also shown quantitative differences when simulating pathologies with EP models [6].…”
Section: Introductionmentioning
confidence: 99%